Profil Penyandang Diabetes Melitus Tipe 2 Disertai Anemia di Poli Endokrin RSUP Prof. Dr. R. D. Kandou Manado Periode September-November 2023 - Rumengan, Gardenia G. E.; Sedli, Bisuk P.; Rotty, Linda W. A. (Medical Scope Journal, 2025)
Abstract: Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by elevated blood sugar level. Anemia is a hematological disorder that often occurs in T2DM patients due to complication of secondary diseases, such as kidney dysfunction. The potential for anemia in T2DM patients can worsen the complications. This study aimed to determine the profile of T2DM patients with anemia at the endocrine polyclinic of Prof. Dr. R. D. Kandou Hospital from September to November 2023. This was a prospective and descriptive study with a cross-sectional design, using medical records at the endocrine polyclinic. The results showed that T2DM patients with anemia in this study (n=40) were dominated by females (55%) and age group of 45-60 years (62.5%). The average levels in laboratory examination were, as follows: HbA1c was 8.683, hemoglobin was 9.583, creatinine was 3.080, and eLFG was 23.38. Classification of anemia types based on erythrocyte morphology was dominated by hypochromic microcytic anemia, experienced by females (47.5%) and in the age group of 45-60 years (55%). In conclusion, the majority of type 2 diabetes mellitus patients with anemia are females aged 45-60 years who experience hypochromic microcytic anemia. Keywords: type 2 diabetes mellitus; anemia; HbA1c glomerular filtration rate    Abstrak: Diabetes melitus tipe 2 (DMT2) adalah gangguan metabolisme yang ditandai adanya peningkatan gula darah. Anemia merupakan gangguan hematologi yang sering terjadi pada penyandang DMT2 yang disebabkan oleh komplikasi penyakit sekunder, seperti gangguan fungsi ginjal. Potensi anemia pada pasien DMT2 dapat memperburuk komplikasi. Penelitian ini bertujuan untuk mengetahui profil penyandang DMT2 disertai anemia di Poli Endokrin RSUP Prof. Dr. R. D. Kandou periode September–November 2023. Jenis penelitian ialah deskriptif prospektif dengan desain potong lintang, menggunakan data rekam medis Poli Endokrin. Hasil penelitian mendapatkan bahwa pasien DMT2 disertai anemia di RSUP Prof. Dr. R. D. Kandou (n=40), didominasi oleh perempuan (55%) dan kelompok usia 45-60 tahun (62,5%). Rerata nilai HbA1c 8,683, Hb 9,583, kreatinin 3,080, dan eLFG 23,38. Klasifikasi jenis anemia berdasarkan morfologi eritrosit didominasi oleh jenis anemia hipokrom mikrositik yang dialami oleh perempuan (47,5%) dan pada kelompok usia 45-60 tahun (55%). Simpulan penelitian ini ialah mayoritas pasien diabetes melitus tipe 2  disertai anemia terjadi pada perempuan dan kelompok usia 45-60 tahun yang mengalami anemia hipokrom mikrositik. Kata kunci: diabetes melitus tipe 2; anemia; HbA1c; laju filtrasi glomerulus